In silico gene selection strategy for custom microarray design - Dondeti, Vijay R (BioTechniques, 2004)
Microarray technology has become an important tool for studying large-scale gene expression for a diversity of biological applications. However, there are a number of experimental settings for which commercial arrays are either unsuitable or unavailable despite the existence of sequence information. With the increasing availability of custom array manufacturing services, it is now feasible to design high-density arrays for any organism having sequence data. However, there have been relatively few reports discussing gene selection, an important first step in array design. Here we propose an in silico strategy for custom microarray gene selection that is applicable to a wide range of organisms, based on utilizing public domain microarray information to interrogate existing sequence data and to identify a set of homologous genes in any organism of interest. We demonstrate the utility of this approach by applying it to the selection of candidate genes for a custom Xenopus laevis microarray. A significant finding of this study is that 3%-4% of Xenopus expressed sequence tags (ESTs) are in an orientation contrary to that indicated in the public database entry (http://mssaha.people.wm.edu/suppMSS.html)